2020
DOI: 10.5937/fme2004922r
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acceleration coefficients in Particle Swarm Optimization algorithm with application to wind farm layout design

Abstract: Wind energy has become a strong alternative to traditional sources of energy. One important decision for an efficient wind farm is the optimal layout design. This layout governs the placement of turbines in a wind farm. The inherent complexity involved in this process results in the wind farm layout design problem to be a complex optimization problem. Particle Swarm Optimization (PSO) algorithm has been effectively used in many studies to solve the wind farm layout design problem. However, the impact of an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Although the PSO method is a faster convergence algorithm than other optimization algorithms and is used to construct the control scheme [38,[40][41], in contrast to those benefits, the common drawback of optimization methods is the early convergence of the solution towards the local minima. A swarm regeneration technique was added to the PSO algorithm [42].…”
Section: Optimization Methodsmentioning
confidence: 99%
“…Although the PSO method is a faster convergence algorithm than other optimization algorithms and is used to construct the control scheme [38,[40][41], in contrast to those benefits, the common drawback of optimization methods is the early convergence of the solution towards the local minima. A swarm regeneration technique was added to the PSO algorithm [42].…”
Section: Optimization Methodsmentioning
confidence: 99%
“…The blade vibration under flatwise, edgewise, torsional, and extensional deformations were studied, and the first ten modes have been identified for stationary and rotating blade conditions. Wind farm layout design was optimized using particle swarm optimization was examined in [17]. It is found that, the acceleration coefficients impact the final layout quality, leading to better overall energy output.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the modern optimization approaches, meta-heuristic algorithms are exploited to solve nonconvex, nonlinear, and multimodal problems with linear or nonlinear constraints and continuous or discrete vari-ables. For example, the Particle Swarm Optimization Algorithm has been effectively used to solve the wind farm layout design problem [11], or the Dingo Optimi-zation Algorithm for solving continuous engineering problems [12]. Further, an optimal load frequency control is optimally designed using the African Vultures Optimization Algorithm (AVOA) [12].…”
Section: Introductionmentioning
confidence: 99%